On the taxonomical status of Arctodiaptomus dampfi Brehm (Crustacea: Copepoda: Diaptomidae) with comments on A. dorsalis (Marsh) - Eduardo SUÁREZ-MORALES (Journal of Limnology, 2001)
Arctodiaptomus dampfi Brehm is a diaptomid copepod described from Lake Petén, in Guatemala. Due to the fact that the type material is lost and no additional material was available, the taxonomical status of this species remained unclear for more than 65 years. Arctodiaptomus dampfi has been advanced as a synonym of A. dorsalis and some authors followed this position; instead, others recognized this species in regional checklists. We collected zooplankton samples at Lake Petén, A. dampfi type locality, and compared this material with confirmed museum specimens and material from Louisiana, the type locality of A. dorsalis. Our observations with light microscopy and SEM allowed us to state that A. dampfi is in fact a synonym of A. dorsalis and should be excluded from regional lists. This was concluded after examination and comparison of the taxonomically relevant structures in both groups of specimens. Differences between both groups of specimens were slight. We found significative size differences between the Guatemalan population and the other neotropical and nearctic ones, the former being the smallest sized populations known throughout the known distributional range of A. dorsalis.